Hubungan Rating Bintang Terhadap Peran Akuntansi Manajemen Strategis (Studi Empiris Pada Perusahaan Hotel di Sumatera Selatan) - Antonius Singgih Setiawan; Rahmawati Rahmawati (Jurnal Akuntansi, 2017)
This  study  aims  to  test  whether  the  star  rating  as  parameter  of  level  hotel  tobring  a  better  impact  on  the  implementation  of  strategic  management  accounting  role  inthe  management  of  the  hotel  business.  Using  a  sample  of  66  respondents  General Manager/Leader  of  Hotel  in  the  province  of  South  Sumatra  (resepon  rate  88%),  research hypotheses  were  tested  using  regression  analysis.  The  results  showed  that  the  star  ratinghotel a positive impact on the implementation of strategic management accounting role infunctional role of accounting and the use of strategic management accounting techniques.